NIGERIA-RUSSIA RELATIONS: AFTER AND NOW - Agubamah, Edgar (European Scientific Journal, ESJ, 2014)
The relations between Nigeria and the former Union of Soviet Socialist Republics(USSR) now represented by Russia reached its highest crescendo during the Nigerian civil war (1967-1970) anchored by the critical and great support given to the country during the civil war by the Soviet Union, supplying military hardware to the Nigerian armed forces. This opened the door to a great deal of opportunities for developing a longlasting, broad relationship in the security, political, economic and sociocultural spheres. In 1991 the USSR broke up and the Russian Federation replaced it. This work aims to interrogate the dynamics of Nigeria’s relations with both the former USSR and the Russian Federation that replaced it against the background of the many colossal metamorphosis taking place on the global scene and the challenges and prospects for strategic partnership between the two nations in rapidly myriad international political, security and economic environment. For clarity sake this work using the traditional diplomatic theory have been compartmentalize into seven sections:- introduction, theoretical framework, Nigeria-USSR 1960-1991, Nigeria- Russia 1991 to present, Nigeria- Russia strategic partnership, challenges and prospects, and conclusion.